2017
DOI: 10.1155/2017/6935648
|View full text |Cite
|
Sign up to set email alerts
|

Low Hemoglobin among Pregnant Women in Midwives Practice of Primary Health Care, Jatinangor, Indonesia: Iron Deficiency Anemia or β-Thalassemia Trait?

Abstract: Low hemoglobin (Hb) or anemia is common among pregnant women in developing countries which may cause adverse pregnancy outcomes and maternal deaths. Our study aimed to assess Hb level measured by midwives in primary health care facility at rural area of Jatinangor, Indonesia, and to explore whether the anemia was due to iron deficiency (IDA) or β-thalassemia trait (β-TT). Pregnant women (n = 105) had finger prick test for Hb level during a regular antenatal care examination from October to November 2016. Hb le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
3
19
0
3
Order By: Relevance
“…Interestingly, anaemia is only prevalent in 57.1 and 25.9% of β-thalassemia carrier IVS1nt5 (c92 + 5G > C) and HbE (c.79G > A) variants, respectively, indicating that most individuals have normal Hb or are non-anaemic, though they have low SLI. SLI has thus been proven to be a valid discriminating index to distinguish between IDA and β-thalassemia [14], as also shown in our previous study [15]. …”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, anaemia is only prevalent in 57.1 and 25.9% of β-thalassemia carrier IVS1nt5 (c92 + 5G > C) and HbE (c.79G > A) variants, respectively, indicating that most individuals have normal Hb or are non-anaemic, though they have low SLI. SLI has thus been proven to be a valid discriminating index to distinguish between IDA and β-thalassemia [14], as also shown in our previous study [15]. …”
Section: Discussionsupporting
confidence: 64%
“…Studies also reported that maternal anemia is associated with fetal and neonatal well-being [ 11 – 13 ]. The latest study on anemia among pregnant women in Jatinangor-West Java was as high as 21.9% [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to sickle cell, the prevalence of β-thalassemia among children and women in our study was notably higher that the prevalence found in other studies. Mockenhaupt et al [ 11 ] found heterozygous β-thalassemia in 1% of pregnant women enrolled in a cross-sectional study in Ghana Two studies from the 1970’s in Nigeria found a β-thalassemia prevalence of < 1% [ 12 ]; however, in a small clinic-based study in Nigeria, Vincent et al [ 13 ] found that 6% of adults possessed both sickle cell and β-thalassemia genes. A similar prevalence of β-thalassemia has been observed in Pakistan (5–8%, [ 14 ]) and Indonesia (6%, [ 13 ]).…”
Section: Discussionmentioning
confidence: 99%